DIMENSIONS OF HISTORIOGRAPHIC NARRATIVE IN THE MEMOIRS BY MARTYNAS JANKUS - KAUNAS, DOMAS (Knygotyra, 2013)
An owner of a printing house and a publisher, Martynas Jankus (1858–1946) was a citizen of Germany and a Lithuanian of the East Prussian region. He was an active member of the Lithuanian national movement of the 19th – early 20th century. He supported the opposition of the people of the Grand Duchy of Lithuania which was annexed and integrated into the Russian empire in 1795. When the usage of the Lithuanian language in Latin script was banned in 1864–1904, Martynas Jankus started printing illegal books and newspapers in his printing house and transporting them secretly to the Russian empire. He supported publishing “Auszra” and “Varpas” the most influential newspapers of the national movement. In 1918, after the restoration of the independence of the Republic of Lithuania, this veteran of Lithuanian culture and politics was highly appreciated and attracted close attention of journalists. He publicised quite many memoirs about the publishing and distribution of illegal press, known newspaper editors and book authors, printers, and publishers. The greatest value for historiographic research of the book resides in three generalised memoirs that M. Jankus attempted in his late years. They include the publication “Smuggling of Lithuanian books” („Lietuviškų Kningų Kontrabanda“) which was published in the newspaper “Tėvynė” (1918) edited by Lithuanians in the USA, and two unpublished manuscripts: an exhaustive narrative (27 pages) without a title about the state of the Lithuanian press and language during the period of the growth of the national movement, sent to the professor linguist of the Göttingen university (Germany) Eduard Hermann, and the memoirs “An encyclopedia of my adventures” (, Mano prietikių enciklopedija“) written in the form of a scholarly encyclopedic dictionary characterizing the acquaintances of M. Jankus. The advantage of the memoirs lays in the point of view of the author who is a direct participant and observer of the factual events, political and social processes, and characters of persons. Foreign researchers appreciate the knowledge of M. Jankus’ cooperation with the participants of Byelorusian, Polish, and German national and revolutionary movements and assistance in their literary publishing. On the other hand, although this author wrote many published and unpublished memoirs, they were small in size, written in the journalistic style and quite open. Therefore, they raised contradictions and critical comments of the public. Many did not understand the character of M. Jankus, which was conditioned by differences in cultural and religious traditions based on the civil rights of Prussian citizens, implying a much greater religious and political freedom. His publications and opinions were not self-controlled or limited in any way. The author sincerely depicted the positive and negative sides and character of the national movement and its participants. He was among the first to raise the issues of Polonized and estranged Catholic priests and the vices of the book smuggling as a social phenomenon. The Lithuanian society was not matured enough at his time and did not support him. The dethronement of the movements, communities, and leaders that had a national character was not tolerated during M. Jankus’ lifetime; it is not tolerated in modern society, either.